Področja sodelovanja učitelja razrednega pouka s šolsko svetovalno službo pri delu z romskimi učenci - Bezjak, Andreja (Revija za elementarno izobraževanje, 2010)
Knowledge acquired through primary education is not sufficient for the success of Romany pupils. It is also necessary for them to adjust socially, find emotional stability and acquire adequate work habits. Therefore we must provide for Romany pupils as much as possible in the field of education and schooling, since this is the only way for such pupils to be able to smoothly integrate in their future lives. This can be accomplished with the adequate organization of education and schooling. In the article we illustrate the problems that Romany pupils encounter in primary education. The emphasis is on the importance of cooperation between teachers and the school counseling service. A description of their role in teaching Romany pupils is also provided. Further on, the results of our research are presented, which included the participation of school counselors from 38 primary schools in Slovenia. The schools chosen are located in Maribor and the Prekmurje and Dolenjska regions. The research focused on the problems that Romany pupils encounter when entering school, the involvement of school counseling services and the activities that school counselors provide for the easier integration of the Romany pupils into the class and the school. In all aspects of the research, it was verified that there exist problems of differences regarding the region in which the school counselors work (Maribor, the Prekmurje and the Dolenjska regions).
Keywords: vzgoja in izobraževanje; romski otroci; učitelji; šolska svetovalna služba; Romi; osnovne šole